OPTIMASI PRODUKSI SEPATU NIKE PADA PT PRATAMA ABADI INDUSTRI DENGAN MENGGUNAKAN METODE PROGRAM DINAMIK - Nurul Pratiwi; Yulianti Rusdiana (LPPM Universitas Bina Bangsa, 2023)
This considers points to discover out how to optimize Nike shoe items at PT Pratama Abadi. The strategy utilized in analyzing the is the recursive energetic programming strategy. To anticipate the sum of generation that must be delivered within the future utilizing straight relapse, at that point to calculate generation costs that must be least and benefits in agreement with the schedulling energetic programming strategy is utilized. From the figure comes about on Nike shoe generation information January-December 2021, the show for the coming period is as takes after:Ŷ = 44.150 + 332 X. So the Nike shoe generation plan for the another 12 periods Jnauary- december 2021 is (44.931, 45.267, 45.602, 45.936, 46.272, 46.607, 46.941, 47.277, 47.621, 47.946, 48.282, 48.616, pairs of shoes). To play down generation costs, the energetic programming strategy is utilized to get a least add up to taken a toll of Rp. 1.347.093.600,